Pre-harvest factors affecting yield, quality and shelf life of mango cv. Amropali (Research in Agriculture Livestock and Fisheries, 2015)
An experiment was conducted to investigate the effect of six pre-harvest treatments on yield, quality and shelf life of a particular Mango cv. Amropali under field condition. The experimental factors were Control, Decis and Savin @ 2 ml L-1, Pheromone trap, Boron 2 mg L-1 and Magic growth @ 2 ml L-1. The plants were of age about 15 years at BAU Germplasm Centre- FTIP, Bangladesh Agricultural University (BAU), Mymensingh during January to July 2013. The experiment was laid out in a Randomized Completely Block Design (RCBD) with three replications. Amropali produced higher number of fruits plant-1 when treated with Boron @ 2 ml L-1 followed by Magic growth 2mlL-1.Maximum number of fruits plant-1, higher yield plant-1 and higher TSS% were recorded in the treatment Boron 2mlL-1. Boron treatment also extended the shelf life of mango as well. The maximum shelf life was found from large sized fruits. Similar performance on yield, quality and shelf life were obtained from Magic growth treatment @ 2 ml L-1 followed by pheromone trap treatment. Control treated fruits exhibited the minimum number of fruits per plant with lower quality but better TSS%. Smaller fruits were obtained from untreated control plants.Res. Agric., Livest. Fish.2(2): 279-286, August 2015